Pengaruh Perendaman Kulit Buah Cokelat (Theobroma cacao)Terhadap Kualitas Minyak Goreng Bekas - Mulia Aria Suzanni; Dina Akmila; Raihanaton Raihanaton; Rizki Andalia; Saudah Saudah; Irhamni Irhamni (Fakultas Teknik, 2020)
The use of waste oil that can cause health problems. The disturbance is caused by the high peroxide number triggered by oxidation and hydrolysis of oil in the presence of free fatty acids and high water content. Reuse of waste oil can be done with several alternatives such as the addition of natural antioxidants or synthesis. This study aimed to determine the effect of soaking wet and dry chocolate fruit on the quality of waste oil. The parameters seen are water content, acid numbers, peroxide numbers and free fatty acid levels. The moisture content was determined by the oven drying method, acid numbers and free fatty acid levels by the alkalimetry titration method, and peroxide number by the iodometry method. The results showed that the waste oil soaked on the exocarp of dried cacao is more optimal in reducing the peroxide number by 38.71%, while soaking with wet exocarp is only 12.14%. Moisture content increased by 0.08% on soaking with the exocarp of dried cacao, whereas wet exsocarp is 1.63%. Acid number increased 17.42% in soaking with the exocarp of dried cacao, whereas wet exocarp is 36%. Free fatty acid levels increased 0.64% in dumping with dried exocarp, while soaking with the exocarp of wet cacao increased by 0.82%.